Design and Fabrication of a Dual‐Photoelectrode Fuel Cell towards Cost‐Effective Electricity Production from Biomass. Issue 1 (20th December 2016) - Zhang, Bingqing; Fan, Wenjun; Yao, Tingting; Liao, Shichao; Li, Ailong; Li, Deng; Liu, Mingyao; Shi, Jingying; Liao, Shijun; Li, Can
Abstract: A photo fuel cell (PFC) offers an attractive way to simultaneously convert solar and biomass energy into electricity. Photocatalytic biomass oxidation on a semiconductor photoanode combined with dark electrochemical reduction of oxygen molecules on a metal cathode (usually Pt) in separated compartments is the common configuration for a PFC. Herein, we report a membrane‐free PFC based on a dual electrode, including a W‐doped BiVO4 photoanode and polyterthiophene photocathode for solar‐stimulated biomass‐to‐electricity conversion. Air‐ and water‐soluble biomass derivatives can be directly used as reagents. The optimal device yields an open‐circuit voltage ( V OC ) of 0.62 V, a short‐circuit current density ( J SC ) of 775 μA cm −2, and a maximum power density ( P max ) of 82 μW cm −2 with glucose as the feedstock under tandem illumination, which outperforms dual‐photoelectrode PFCs previously reported. Neither costly separating membranes nor Pt‐based catalysts are required in the proposed PFC architecture. Our work may inspire rational device designs for cost‐effective electricity generation from renewable resources. Abstract : Electrode cooperation : A dual‐photoelectrode photo fuel cell (PFC) is constructed by coupling a semiconducting polyterthiophene photocathode with a W‐doped BiVO4 photoanode, which is capable of converting solar and biomass energy simultaneously into electricity through the photoelectrochemcial oxygen reduction and biomass oxidation at the cathodic and anodic sides, respectively. The device yields a power density of 82 μW cm −2 that outperforms previously reported dual‐photoelectrode PFCs.